Otherproof - Landowski, Eric (2016)
Delimiting a field of study and fixing a corpus of texts that will serve as the basis for the analysis are not the only tasks facing semiotics. There is another dimension, that of intersubjectivity, which raises interesting problems between the semiotic analyst and his sources of information. That otherness has an ethical framework, whose rigorous compliance depends on the study of a certain matter without falling into stereotypes or deformations. It is therefore a question of overcoming the univocal and exclusive view of the researcher, to give way to the voice of the other, to that symbolic space of dialogue and cultural exchange that enriches perspectives and establishes currents of empathy between the student and his object of study.